Investor Behavior In Investment Decisions - Violita, Futri; Sofyaun, Ashari; Matyani, Matyani (Riwayat: Educational Journal of History and Humanities, 2025)
Quantitative approach as a type of research with questionnaires as a data collection tool. The population in the study were class A students of the management study program, class of 2021, Balikpapan University with a sample of 94 people. The data analysis method used multiple linear regression analysis for hypothesis testing, and the coefficient of determination. The results of the study showed that partially, the variables overconfidence, and investment knowledge had a positive and significant effect on Investment Decisions, while the variables investment motivation and risk tolerance had no effect.